KONSEP PENDIDIKAN ISLAM MULTIKULTURAL DALAM MENCIPTAKAN HARMONISASI KELEMBAGAAN - M Muizzuddin; Ahsantudhonni Ahsantudhonni (JP : JURNAL PENDIDIKAN, 2020)
Abstract: This study will discuss the Concept of Multicultural Islamic Education in Creating a Harmonious Institutional System: A Case Study in the Madrasah Aliyah Mamba'us Sholihin Suci-Manyar-Gresik. In theory, Institutions are the rules that apply in society that are agreed upon by community members as something that must be followed and obeyed (having the power of sanctions) with the aim of creating order and certainty of interactions among community members. In this article we will describe the initial concept of the values of multicultural Islamic education, then we will describe the concept of an institutional system, and end with a presentation of the results of research on the Role of Multicultural Islamic Education in Creating a Harmonious Institutional System. This study uses an interpretive paradigm with a qualitative approach, a type of case study. Collecting data using unstructured interview techniques, non-participant observation, and documentation study. This study found the conclusion that the values of multicultural Islamic education that developed in the institution helped make the institution into harmony. These values include At-Tawassuth (moderate), At-Tasamuh (tolerant), At-Ta'awun (please-help), and At-Tawazun (harmony).Keywords: Institutional, Multicultural Islamic Education Values